GOOD NURSING PRACTICES FOR PATIENTS UNSING MECHANICAL VENTILATION. - Papa Pazos, Carolina; Morais Soares, Francisco Mayron; Cordeiro Barroso, Luana; Cavalcante de Sousa, Gustavo Mitsuo; da Silva Rodrigues, Gabriel Italo; Batista Mesquita, Kirley Kethellen; Gomes Freitas, Julyana; Rigoberto Cavalcante Andrade, Italo (Journal of Nursing UFPE / Revista de Enfermagem UFPE, 2020)
Objective: to identify nursing care for patients on mechanical ventilation. Method: this is a quantitative, descriptive and cross-sectional study with patients on mechanical ventilation admitted to the Intensive Care Center, divided into surgical and clinical. For data analysis, the Statistical Package for Social Science program (version 20) was used. Results: it is revealed, as for nursing care, that keeping the head up to 30º was the most found in 77.9% of cases, and checking TOT or TQT positioning was the least found, reaching 61.9% of the cases. prescriptions. Conclusion: it is concluded that there is still a need to organize the team in the implementation of the prescribed interventions for the patient using mechanical ventilation, thus reducing the length of stay, complications and infections, and weaning to occur. a shorter time.